2019
DOI: 10.1063/1.5111681
|View full text |Cite
|
Sign up to set email alerts
|

Turbulent transport and mixing in the multimode narrowband Richtmyer-Meshkov instability

Abstract: The mean momentum and heavy mass fraction, turbulent kinetic energy, and heavy mass fraction variance fields, as well as the budgets of their transport equations, are examined at several times during the evolution of a narrowband Richtmyer-Meshkov instability initiated by a Mach 1.84 shock traversing a perturbed interface separating gases with a density ratio of 3. The results are computed using the 'quarter scale' data from four algorithms presented in the θ -group study of Thornber et al. [Phys. Fluids 29, 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 57 publications
3
19
0
Order By: Relevance
“…The second term T II is the turbulent-mass-flux coupling term, so named because the product of density and u i = u i − u i can be interpreted as a turbulent mass flux that vanishes for a constant-density flow. As a contribution to T II , the product − u i ∂p/∂x i is called the buoyancy production term (Schilling & Latini 2010;Thornber et al 2019) or the mean pressure work term (Chassaing et al 2010). The third term T III is the pressure-dilatation term.…”
Section: Appendix F Mdtke Analysis: Additional Detailsmentioning
confidence: 99%
“…The second term T II is the turbulent-mass-flux coupling term, so named because the product of density and u i = u i − u i can be interpreted as a turbulent mass flux that vanishes for a constant-density flow. As a contribution to T II , the product − u i ∂p/∂x i is called the buoyancy production term (Schilling & Latini 2010;Thornber et al 2019) or the mean pressure work term (Chassaing et al 2010). The third term T III is the pressure-dilatation term.…”
Section: Appendix F Mdtke Analysis: Additional Detailsmentioning
confidence: 99%
“…It is interesting to note that κ 0 is very similar to the weighted average wavenumberk introduced in Eqn. 33. For example, for the m = −2 case at a bandwidth of R = 128, κ 0 = 23.46 andk = 22.62.…”
Section: Mixing Measuresmentioning
confidence: 99%
“…In the largest such study to date (known as the θ -group collaboration), Thornber et al (2017) showed that good agreement is obtained for various integral measures such as the mixing layer width, mixedness and total fluctuating kinetic energy across eight independent algorithms. In a follow-up paper, Thornber et al (2019) computed the transport equation budgets for the mean momentum, mean heavy fluid mass fraction, heavy fluid mass fraction variance and specific turbulent kinetic energy to provide useful benchmark data for the development of closure models for these quantities. There is still a lack of understanding with regards to the behaviour of the mixing layer during the transitional period between linear growth and fully developed turbulence, however.…”
Section: Introductionmentioning
confidence: 99%
“…In a follow-up paper, Thornber et al. (2019) computed the transport equation budgets for the mean momentum, mean heavy fluid mass fraction, heavy fluid mass fraction variance and specific turbulent kinetic energy to provide useful benchmark data for the development of closure models for these quantities. There is still a lack of understanding with regards to the behaviour of the mixing layer during the transitional period between linear growth and fully developed turbulence, however.…”
Section: Introductionmentioning
confidence: 99%